#### Answer

-2$\frac{1}{2}$

#### Work Step by Step

-$\frac{3}{2}$+($\frac{1}{2}$-$\frac{3}{2}$)=
-$\frac{3}{2}$+$\frac{1-3}{2}$=
-$\frac{3}{2}$+$\frac{-2}{2}$=
$\frac{-3-2}{2}$=-$\frac{5}{2}$=-2$\frac{1}{2}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

-2$\frac{1}{2}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.